Implementasi Peraturan Menteri Dalam Negeri No 41 tahun 2012 tentang Pedoman Penataan Pemberdayaan Pedagang Kaki Lima di kelurahan Suka Maju Kecamatan Medan Johor - Aziz, Ahmad Robiul; Zainuddin, Zainuddin; Hartono, Budi (Mahesa Research Center, 2022)
The arrangement of street vendors is felt to be very important to create an orderly and comfortable atmosphere for the people of Medan Johor village. The chaotic and disorganized situation that occurred around the Medan Johor sub-district was caused by street vendors who were not well organized. To find out the implementation of the Minister of Home Affairs Regulation No. 41 of 2012 concerning Guidelines for the Empowerment of Street Vendors in Suka Maju Village, Medan Johor Subdistrict, this research was conducted. The focus of the research is on implementing the policy of the Minister of Home Affairs Regulation. Structuring the empowerment of street vendors requires evaluation and relocation. The purpose of this study is to determine the extent to which Ministerial Regulation No. 41 of 2012 is applied to the Suka Maju sub-district, Medan Johor sub-district. Data was collected through observational studies, interviews and documentation studies. Further analysis is carried out. The methodology in this research is descriptive qualitative. The results of the study show that there is a need for more optimal socialization. This study concludes that the relocation of street vendors in Suka Maju sub-district, Medan Johor sub-district has not run optimally and that many traders still do not want to be relocated to places that have been provided by the Suka Maju sub-district, Medan Johor sub-district.